Effect of work status on leakage and contact pressure of C/C composite finger seal. (March 2017) - Wang, Li-Na; Chen, Guo-Ding; Su, Hua; Lu, Fei; Zhang, Yan-Chao
The effect of a seal device on the performance of aeroengines is obvious. As well as the complicated operating state of aeroengines also has important influence on seal device performance. Finger seal is a new seal device, which has been extensively studied recently. However, so far there is little work about finger seal's dynamic performance considering work status. For this reason, finger seal's dynamic performance considering work status is proposed using equivalent dynamic model with distributed mass in this paper. The effects of the precession and nutation incline of rotor on the finger seal's performance are investigated. Meanwhile, density and preparation direction of fiber bundle have influence on its dynamic performance and that is studied under the rotor precession incline. Based on this, it is shown that the effect of rotor precession incline on the finger seal dynamic performance is obvious, thus it is necessary to consider the effect of the factor on finger seal dynamic performance. The present work is conducive to promote dynamic analysis technology of finger seal to engineering application, and also improve the theoretical research system and methodology of finger seal.